Kerawanan Bencana Alam Sebagai Ancaman Nirmiliter Studi Penataan Infrastruktur Rawan Bencana di Kabupaten Magelang - Aditiawan WSP; Fourita DM; Tarigan (PPM Sdirjianbang Akademi Militer, 2026)
This study aims to analyze disaster vulnerability in Magelang Regency and visualize it through a three-dimensional (3D) topographic map model. Magelang Regency has complex geological and geomorphological characteristics, which contribute to potential hazards such as volcanic eruptions, lahars, landslides, floods, and earthquakes. The research employs a spatial analysis approach by integrating topographic data, land-use information, and disaster risk zoning into a 3D visualization model. The resulting 3D map presents realistic elevation features overlaid with disaster vulnerability zones classified into low, medium, and high-risk levels. The findings indicate that 3D visualization significantly enhances spatial understanding of disaster risks compared to conventional two-dimensional maps, making it a more effective tool for mitigation planning and strategic decision-making. From a Defense Civil Engineering perspective, this model serves as an analytical tool for planning disaster infrastructure, supporting military operations other than war (MOOTW), and strengthening regional resilience. This study is expected to provide valuable references for local governments, disaster management agencies, and military education institutions in disaster risk reduction and preparedness efforts.